2011
DOI: 10.1093/jxb/err243
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a dual-affinity nitrate transporter MtNRT1.3 in the model legume Medicago truncatula

Abstract: Primary root growth in the absence or presence of exogenous NO(3)(-) was studied by a quantitative genetic approach in a recombinant inbred line (RIL) population of Medicago truncatula. A quantitative trait locus (QTL) on chromosome 5 appeared to be particularly relevant because it was seen in both N-free medium (LOD score 5.7; R(2)=13.7) and medium supplied with NO(3)(-) (LOD score, 9.5; R(2)=21.1) which indicates that it would be independent of the general nutritional status. Due to its localization exactly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 54 publications
1
76
0
Order By: Relevance
“…Thus, we will refer to Pro1404 as a dual affinity transporter. To our knowledge, only two other transporters, a potassium and a nitrate transporter from plants, have been shown to be dual-affinity transporters with a biphasic kinetics by the use of an ectopic expression approach similar to the one shown here (21)(22)(23). In the case of the nitrate transporter, the alternation from the high-affinity to the lowaffinity mode and vice-versa is controlled by phosphorylation (24).…”
Section: Resultsmentioning
confidence: 96%
“…Thus, we will refer to Pro1404 as a dual affinity transporter. To our knowledge, only two other transporters, a potassium and a nitrate transporter from plants, have been shown to be dual-affinity transporters with a biphasic kinetics by the use of an ectopic expression approach similar to the one shown here (21)(22)(23). In the case of the nitrate transporter, the alternation from the high-affinity to the lowaffinity mode and vice-versa is controlled by phosphorylation (24).…”
Section: Resultsmentioning
confidence: 96%
“…A quantitative genetic approach allowed us to identify a major QTL involved in the control of M. truncatula radicle elongation in post-germination phase in both N-free medium and medium supplied with 5 mM nitrate. The MtNPF6.8 gene, which coincided with the peak of the QTL, appeared to be a significant candidate involved in the control of primary root growth and nitrate-sensing (Morère-Le Paven et al 2011). Further experiments using npf6.8 mutants indicated that MtNPF6.8 has the hallmarks of a nitrate sensor (Fig.…”
Section: Primary Nitrate Responsementioning
confidence: 91%
“…In this species, nitrate has an inhibitory effect on primary root growth at low and high concentrations in two different ecotypes, A17 and R108 (Yendrek et al 2010;Morère-Le Paven et al 2011;Pellizzaro et al 2014). A quantitative genetic approach allowed us to identify a major QTL involved in the control of M. truncatula radicle elongation in post-germination phase in both N-free medium and medium supplied with 5 mM nitrate.…”
Section: Primary Nitrate Responsementioning
confidence: 99%
“…AtNPF6.3 (AtNTR1.1, CHL1), one of 53 proteins in the NPF of Arabidopsis, can transport nitrate (99) and auxin (100) as can the M. truncatula homolog MtNRT1.3 (101,102). In this context, indole acetic acid uptake by isolated soybean symbiosomes as reported (103) may be relevant.…”
Section: Soybean Symbiosome Proteomementioning
confidence: 97%